Face, grace and disgrace: an essay on the phenomenon of spying through the prose of Gabriela Adameșteanu, Blaga Dimitrova, and Tzvetan Marangozov (Colloquia Comparativa Litterarum, 2025)
The text is concentrated on the semantic net of a few main topics: face, difference, and indifference (ataraxia), personality and impersonality, following and spying. Three novels which represent different totalitarian versions are in the focus of the analysis. The parallels point out the propinquity between the novels and their conception of the human “being and time”, and especially the phenomenon of the face. The face never marks only its physical manifestation. It is an essential divine mark of infinite love and grace. It is a place of supreme ordeal and supreme feast. The place where the man has to do the most important choice in his life.
Keywords: Balkan literatures; totalitarian experience; myth; personality; otherness; holiness; sense